Digital Communication and Social Change Movements: Case Study of the Utilization of the Instagram Account Wahanavisi_id in the Educational Program for Supporting Children's Reading Houses in Papua - Fitriani, Annisya; Hermanto, Rudi (International Journal Labs, 2025)
This research discusses the use of the Instagram account @wahanavisi_id in supporting the Bantu Rumah Baca Anak Papua program, a social initiative to improve the literacy of Papuan children through the provision of reading rooms. The main objective of this research is to explore the digital communication strategy implemented by the Instagram account, as well as its impact on public awareness and participation in education-based social movements. Using Pierre Lévy's Collective Intelligence theory, this research identifies the role of connectivity, active participation and collaboration in mobilizing support through social media. The results show that Instagram is not only an effective communication tool, but also a platform to build social solidarity and raise awareness of education in Papua. Through the use of visual elements, emotional narratives, and interactive features of Instagram, @wahanavisi_id succeeded in inviting audiences to participate in this social campaign, both through donations, information sharing, and collaboration with various parties. These findings contribute to the digital communication literature, especially in the context of new media-based social movements in Indonesia.